Necrotizing Pneumonia: Komplikasi Langka dari Pneumonia pada Anak yang Menggunakan Rokok Vape - Laporan Kasus: Laporan Kasus - Simanjuntak, Arya Marganda; Nasution, Riza Iriani; Ridar, Elmi; Cesilia, Citra; Candra, Riky (PT Kalbe Farma Tbk., 2026)
Introduction: Necrotizing pneumonia (NP) is a severe complication of pneumonia characterized by lung parenchymal destruction, cavitation, and significant morbidity in children. It is commonly associated with virulent bacterial infections and inadequate response to initial antibiotic therapy. Certain risk factors, including exposure to cigarette smoke and electronic cigarettes (vaping), may influence immune defense mechanisms and contribute to disease severity. Case: A 15-year-old boy presented to the emergency room with shortness of breath, persistent fever, productive cough, and bloody sputum for 2 weeks. He had no history of TB contact but had used vape and smoke cigarettes regularly during the past year. Physical examination revealed tachypnea and rhonchi on auscultation. Chest radiography demonstratedextensive consolidation, and thoracic CT scan showed cavitary lesions consistent with necrotizing pneumonia. GeneXpert sputum testing was negative for Mycobacterium tuberculosis. The diagnosis was necrotizing pneumonia (NP). Broad-spectrum antibiotics and supportive management were administered. Discussion: Early recognition of NP in children is essential to prevent complications and prolonged hospitalization. Inhalational exposures such as vaping may compromise pulmonary defense and potentially exacerbate infectious processes.Conclusion: Necrotizing pneumonia should be suspected in children with severe pneumonia unresponsive to initial therapy. Timely diagnosis and appropriate management are critical to improving clinical outcomes. Vaping is likely to play a role in this rare complication because its chemicals can damage the pulmonary defense, making it susceptible to and potentially worsening infection. Future research and awareness towards vape health effects should be enhanced to suppress the use, especially in children.